Pro Swimbait & Co. : Fish On / Muhammad Izz Husaine ...[et al.] - Husaine, Muhammad Izz; Ismail, Muhammad Hidayat; Nik Amran, Nik muhamad Hazwan; Mohd Arham, Nurul Hazirah (2019)
Nowadays, the lure or swim bait has been a main concern of the fishers because of different types of fish need a specific lure for it. The fishers realize that choosing a lure or a swim bait is the main priority and try to choose the best lure for a big catch. The new innovation which is the material that been used to make the lure was wood for its body. The wood that is used is high quality and the weight of is suitable for every type of water. Moreover, the lure will float when the caster pull it fast, anglers call it as top water casting but if they pulled it slow, the lure will swim under the water which is called as bottom casting. It is free to move depends on the user. Besides, for the hook is made from forged hi carbon and vanadium steel treble which makes the lure strong, durable and user friendly. It can hold strong pulling from the fish. The best material that is used to make it durable. When casting at any spot, the fish that will chase the lure usually have an extreme mouth that can cause damage to the lure but not for the Pro SwimFish.